2020
DOI: 10.1007/s12540-020-00655-3
|View full text |Cite
|
Sign up to set email alerts
|

Design of Eutectic High Entropy Alloys in Al–Co–Cr–Fe–Ni System

Abstract: In the present work, a simple approach is proposed for predicting the compositions of eutectic high entropy alloys (EHEAs) in Al-Co-Cr-Fe-Ni system. It is proposed that eutectic lines exist between certain eutectic alloys in this system and, as a result, new eutectic or near-eutectic compositions can be obtained by mixing the alloys which are located on the same eutectic line. The approach is applied for a series of experimentally verified eutectic alloys and new eutectic or near-eutectic alloys are designed f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…It has been reported that the formation of a new BCC phase in the AlxCoCrFeNi alloy system can be associated with the lattice distortion induced by the atomic size difference [3]. In recent years, eutectic high-entropy alloys (EHEAs) have emerged as one of the most popular classes of HEAs as they exhibit a nano-lamellar eutectic microstructure composed of BCC and FCC phases, which improve the material's strength, ductility, and microstructure stability [6][7][8]. It was proposed by Lu et al in 2014 [9] that an as-cast AlCoCrFeNi 2.1 comprising the CoCrFe phase (ductile FCC phase) and the NiAl phase (high-strength B2 phase) demonstrates promising properties with excellent strength (1186 MPa) and ductility (22.8%) [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the formation of a new BCC phase in the AlxCoCrFeNi alloy system can be associated with the lattice distortion induced by the atomic size difference [3]. In recent years, eutectic high-entropy alloys (EHEAs) have emerged as one of the most popular classes of HEAs as they exhibit a nano-lamellar eutectic microstructure composed of BCC and FCC phases, which improve the material's strength, ductility, and microstructure stability [6][7][8]. It was proposed by Lu et al in 2014 [9] that an as-cast AlCoCrFeNi 2.1 comprising the CoCrFe phase (ductile FCC phase) and the NiAl phase (high-strength B2 phase) demonstrates promising properties with excellent strength (1186 MPa) and ductility (22.8%) [9].…”
Section: Introductionmentioning
confidence: 99%
“…HEAs have come to be defined as multi-principal element alloys (MPEAs) with at least five elements all having equal, or near-equal, atomic ratios [1][2][3][4]. The consensus is also that HEAs form random single-phase solid solutions [5,6], although various dual-phase HEAs have been accepted [7][8][9]. Whether a HEA is single or dual-phase, the underlying lattices are generally highsymmetry, simple-solid solutions such as face-centered-cubic (FCC), body-centered-cubic (BCC) or hexagonal close-packed (HCP) [10].…”
Section: Introductionmentioning
confidence: 99%